From Social Market Economy Values to ESG Indicators: An MBA-OrientedFramework for Responsible Management Education - Martin Dahl; Karol Strzała; Anna Phirtskhalashvili; Tomás Gutiérrez Roa; Amina Taurabi (Universitas Pancasakti Tegal, 2026)
This article examines how the normative principles of the Social Market Economy (SozialeMarktwirtschaft) can serve as a philosophical foundation for interpreting Environmental, Social, andGovernance (ESG) indicators in MBA education. An integrative literature review synthesisedscholarship from three fields—ordoliberal economic philosophy, ESG measurement, and responsiblemanagement education—while curriculum mapping translated theoretical correspondences intoassessable learning outcomes. The article proposes a ten-row conceptual matrix linking SGR-derivedprinciples (competitive order, rule-based governance, liability, social balance, Vitalpolitik,sustainability, interdependence of orders, transparency and accountability, the green regulatoryframework, and fiscal responsibility) to ESG indicator families and to MBA competencies aligned withBloom's revised taxonomy and with established sustainability competency frameworks. The findingsshow that ESG indicators gain analytical coherence and pedagogical utility when grounded in the SGRtradition rather than treated as a neutral compliance checklist. The framework is operationalisedthrough a five-module MBA curriculum aligned with selected PRME principles and the fivesustainability competencies of Wiek, Withycombe, and Redman (2011). Implications for curriculumdesign and an agenda for empirical testing are discussed.